Energy Model for a Differential Guide Mobile Robot using Modelica Language (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Energy consumption is an important element in the autonomy of mobile robots. In this paper, an energy model has been developed in Modelica language. The power of the Modelica® language is shown by simulating the energy model for a differential guide mobile robot as well as the motors. The model is tested with typical motor energy, mixed energy models, and a trapezoidal velocity as input.